The Feasibility of Applying Waste Concrete as Coarse Aggregates in New Concrete - Nguyen, T. H.; Nguyen, T. T. T.; Nguyen, T. T. H.; Phan, V. T. (Engineering, Technology & Applied Science Research, 2022)
This paper presents a study on the possibility of replacing natural coarse aggregates with recycled aggregates in concrete in terms of strength, namely compressive strength and flexural strength. The concrete was designed to have a 25MPa compressive strength and an 8cm slump. The replacement rates of natural aggregates with recycled coarse aggregates were 0%, 10%, 15%, and 20%. The test samples were compressed to determine their strength value after 28 days of curing. The research results give a more complete assessment of the efficiency of the use of recycled raw aggregates instead of natural aggregates in concrete. The results indicate that using recycled aggregates is feasible due to the small decrease in concrete strength. The experiment shows that up to 20% replacement, the recorded reduction in the strength of concrete is lower than 15%. However, it is indispensable that the strength of concrete should be enhanced when recycled aggregates are used. According to previous works, fiber reinforcement may be an effective solution. Therefore, to further develop research using recycled aggregates, it is necessary to consider using different fibers to strengthen the concrete. The fiber content can be used in the range of 0-1% of the weight of concrete.